2020
DOI: 10.21203/rs.3.rs-17239/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CCL3 contributes to secondary damage after spinal cord injury

Abstract: Background: Secondary damage after spinal cord injury (SCI) is characterized by a cascade of events including hemorrhage, apoptosis, oxidative stress and inflammation which increase the lesion size which can influence the functional impairment. Thus, identifying specific mechanisms attributed to secondary injury is critical in minimizing tissue damage and improving neurological outcome. In this work, we are investigating the role of CCL3 (Macrophage inflammatory protein 1- α, MIP-1α), a chemokine involved in t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
(59 reference statements)
1
16
0
Order By: Relevance
“…Expression induced by pro-inflammatory stimulators, such as LPS, TNFα and IL-1β, and neuronal injury [ 163 ]…”
Section: Main Textmentioning
confidence: 99%
“…Expression induced by pro-inflammatory stimulators, such as LPS, TNFα and IL-1β, and neuronal injury [ 163 ]…”
Section: Main Textmentioning
confidence: 99%
“…Besides, we also observed that CCL3 was also inhibited by cordycepin. CCL3 recruits neutrophils through binding to the CCR1 on the neutrophil surface, neutrophil recruitment in mice with CCL3 de ciency signi cantly decreased as reported [65,66]. Moreover, TNF-α and IL-1β mobilize neutrophils and induce adhesion molecule expression on cerebral endothelial and glial cells, thereby promoting neutrophil accumulation and migration into CNS [65,67,68].…”
Section: Discussionmentioning
confidence: 71%
“…[17]. By binding to receptors on immune cells, CCL3 promotes the production of in ammatory cytokines, and overactive of CCL3 has a direct detrimental effect on the prognosis of the disease [16,24].…”
Section: Discussionmentioning
confidence: 99%